2017
DOI: 10.5194/acp-17-6113-2017
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stratospheric water vapor over the summertime continental United States and the role of overshooting convection

Abstract: Abstract. The NASA ER-2 aircraft sampled the lower stratosphere over North America during the field mission for the NASA Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS). This study reports observations of convectively influenced air parcels with enhanced water vapor in the overworld stratosphere over the summertime continental United States and investigates three case studies in detail. Water vapor mixing ratios greater than 10 ppmv, which is much h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…High-altitude aircraft has observed localized convective hydration (Anderson et al, 2012;Corti et al, 2008;Danielsen, 1993;Hanisco et al, 2007;Herman et al, 2017;Khaykin et al, 2009;Kley et al, 1982;Smith et al, 2017); however, our calculations show that these events contribute <1% to the global stratospheric water vapor budget. Even if we narrow the range of impact to the tropical lower stratosphere (less than 30°latitude) the impact is 1-2%, much smaller than the 5-10% tropical increase computed by S14 using MERRA reanalysis.…”
Section: Impact Of Convectionmentioning
confidence: 54%
See 2 more Smart Citations
“…High-altitude aircraft has observed localized convective hydration (Anderson et al, 2012;Corti et al, 2008;Danielsen, 1993;Hanisco et al, 2007;Herman et al, 2017;Khaykin et al, 2009;Kley et al, 1982;Smith et al, 2017); however, our calculations show that these events contribute <1% to the global stratospheric water vapor budget. Even if we narrow the range of impact to the tropical lower stratosphere (less than 30°latitude) the impact is 1-2%, much smaller than the 5-10% tropical increase computed by S14 using MERRA reanalysis.…”
Section: Impact Of Convectionmentioning
confidence: 54%
“…Both convection and diabatic upwelling supply water vapor to the upper tropical troposphere and play a role in determining the altitude of the tropopause (Randel & Wu, ; Son & Lee, ; Thuburn & Craig, ; Zhou & Holton, ). Midlatitude aircraft measurements suggest that overshooting convection can also move water directly into the stratosphere bypassing dehydration by the cold trap (Anderson et al, ; Danielsen, ; Hanisco et al, ; Herman et al, ; Smith et al, ). Recent tropical aircraft measurements show tropical convective overshoots reaching into the lower stratosphere (Corti et al, ; Khaykin et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that TTL water vapor variability is mainly controlled by TTL temperature variability (Mote et al, 1996;Holton and Gettelman, 2001;Fueglistaler et al, 2009). In particular, variations in the BDC and QBO play key roles (Fueglistaler and Haynes, 2005;Geller et al, 2002;Liang et al, 2011;Liess and Geller, 2012;Calvo et al, 2010;Randel et al, 2006;Dessler et al, 2013Dessler et al, , 2014Tao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Air enters the stratosphere from the tropical troposphere mainly through the tropical tropopause layer (TTL, ∼ 15-18 km) (Sherwood and Dessler, 2000;Fueglistaler et al, 2009), which serves as a transition region between the troposphere and stratosphere. It is generally recognized that the coldest temperatures in the TTL act like a "cold trap" that provides primary control on the amount of water vapor entering the lower stratosphere (Mote et al, 1996;Holton and Gettelman, 2001). Large interannual variations of TTL water vapor have been observed and attributed to a set of physical processes that affect water vapor by varying TTL temperatures, such as the quasi-biennial oscillation (QBO) (Geller et al, 2002;Fueglistaler and Haynes, 2005;Liang et al, 2011;Liess and Geller, 2012;Randel and Jensen, 2013;Wang et al, 2015;Tao et al, 2015) and the Brewer-Dobson circulation (BDC) (Randel et al, 2006;Calvo et al, 2010;Dessler et al, 2013Dessler et al, , 2014Fueglistaler et al, 2014;Gilford et al, 2016).…”
Section: Introductionmentioning
confidence: 99%